Culturally Responsive Teaching in Social Studies Education: A Systematic Literature Review - Muhammad Yamin; Lutfin Haryanto (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
This systematic literature review (SLR) synthesizes current evidence on the implementation of Culturally Responsive Teaching (CRT) in Social Studies Education, with particular attention to the integration of local wisdom. Following the PRISMA 2020 guidelines and the SPICE framework, relevant studies were identified from the Scopus database (2000–2026). After the screening process, empirical studies were analyzed using thematic synthesis to address four research questions concerning CRT implementation, local wisdom integration, pedagogical characteristics, and educational outcomes. The findings indicate that CRT is implemented through culturally inclusive curricula, dialogic pedagogy, inquiry-based learning, local history, multicultural citizenship education, and technology-supported learning. Local wisdom is integrated through cultural experiences, indigenous knowledge, community narratives, local history, and cultural values, strengthening contextual learning and cultural identity. The review also identifies contextual, dialogic, critical, inclusive, and transformative pedagogical characteristics. Consequently, this review proposes the Local Wisdom-Based Culturally Responsive Social Studies Pedagogy model as a conceptual framework for advancing culturally responsive, socially just, and contextually relevant social studies education.